Revision of the rare Mesoamerican bee genus Mexalictus (Hymenoptera: Halictidae) with the description of 21 new species - Dumesh, Sheila (Zootaxa, 2013)
The Mesoamerican bee genus Mexalictus (Hymenoptera: Halictidae: Halictinae) is a group of rare bees which are found at high elevations from southern Arizona (USA) to Panama. The genus is revised using traditional taxonomic approaches. The following twenty one new species are described: M. albofasciatus Dumesh, n. sp., M. anatolii Dumesh, n. sp., M. astriatus Dumesh, n. sp., M. ayalai Dumesh, n. sp., M. benyamini Dumesh, n. sp., M. diversus Dumesh, n. sp., M. jovelus Dumesh, n. sp., M. genalis Dumesh, n. sp., M. gibbsi Dumesh n. sp., M. guatemalensis Dumesh, n. sp., M. hansoni Dumesh, n. sp., M. hondurensis Dumesh, n. sp., M. laurencei Dumesh, n. sp., M. mandibularis Dumesh, n. sp., M. nicaraguensis Dumesh, n. sp., M. punctatus Dumesh, n. sp., M. raavo Dumesh, n. sp., M. sheffieldi Dumesh, n. sp., M. veracruzense Dumesh, n. sp., M. verdazulus Dumesh, n. sp., M. vitriolus Dumesh, n. sp. These and five previously known species are diagnosed, described, illustrated, and keyed. Phylogenetic analysis, based on 43 unordered morphological characters, resulted in 4 equally most parsimonious trees (L=176; Ci=36.4; Ri=56.6). Based upon these results, the subgeneric classification of Mexalictus into Georgealictus and Mexalictus s.str., is resurrected.